(3GdCfhGQ GdZQhjI aj TQM GddeYI GdOeTbjIs - (3eMeO LhGO Hf eMeO Jbj edG cJGHs ((3eMeO Ydj Hf Ndjd GdNhfSGQjs)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf ceG gh Cgdg(B... (3cJGH GdRcGI, haUhdg CQHYI(B...s
(3BNQgG (B:s
(3hjhe JUObg HGdNGJe hgh GdQGHY hGdYTQhf ef Pj GdMLI hgh jhe GdeHGgdI hjhe fRhd gd CJi aj TCfg hgh GdNGeS hGdYTQhfs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3GdJedcGJ h GdhbajGJ (B:s
(3Jedc(B: (3Ydj MajO GdgGOj cGTa GdZWGA, (B1371(3g`s
Keywords: (3abg GdePGgH GdCNQis